Caffeine maternal intake and its effect on low birth weight of newborns - a literature review - Luchowska, Anna; Sroczyńska, Monika; Żaczek, Aleksandra (Journal of Education, Health and Sport, 2022)
Introduction: Caffeine consumption during pregnancy is associated with a number of concerns related to fetal development. The daily amount of caffeine consumed has consequences depending on the doses taken. Aim of the study: The purpose of this study is to present the contemporary knowledge on the relationship between prenatal caffeine exposure and its effects on fetal development with special attention to low birth weight of newborns. Materials and methods: PubMed and Google Scholar medical databases were analyzed by typing the following keywords: caffeine, low birth weight, caffeine consumption during pregnancy, cohort studies. During analyzing the literature, data from 14 scientific articles from the last five years (2017-2022) were used. Results: In most of the articles using cohort studies and meta-analyses based on them, the authors emphasize the link between caffeine consumption and low neonatal birth weight and other health implications among children. However, some argue that caffeine consumption does not significantly affect low birth weight in newborns. Conclusions: The results are inconclusive and the study needs to be continued. Most authors confirm the association between caffeine consumption during pregnant and low birth weight while some do not. It seems reasonable to increase awareness among women about the sources of caffeine, the amount of caffeine consumption and the effects on the fetus before conception.